The bell curve wars: race, intelligence and the future of America - Fraser, Steve (Basic Books, 1995)
The Bell Curve by Richard J. Herrnstein and Charles Murray has generated a firestorm of debate, confirming for some their secret belief in the innate inferiority of certain "races" or ethnic groups, angering many who view the book as an ill-concealed racist manifesto, and worrying untold others who fear the further racial polarization of American society. In The Bell Curve Wars, a group of our country's most distinguished intellectuals dismantles the alleged scientific foundations and criticizes the alarming public policy conclusions of this incendiary book